2022
DOI: 10.3390/jof8050536
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Sporotrichosis Caused by Sporothrix brasiliensis: A 22-Year, Single-Center, Retrospective Cohort Study

Abstract: Pulmonary sporotrichosis is a rare condition. It can present as a primary pulmonary disease, resulting from direct Sporothrix species (spp). conidia inhalation, or as part of multifocal sporotrichosis with multiple organ involvement, mainly in immunocompromised patients. This study aimed to describe the sociodemographic and epidemiological characteristics and clinical course of patients with positive cultures for Sporothrix spp. from pulmonary specimens (sputum and/or bronchoalveolar lavage) at a reference cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…6 On the other hand, Fichman et al found that 78.6% of patients using alcohol in a cohort of 12 patients with pulmonary sporotrichosis. 7 Besides reporting the alcohol consumption by the patients, those studies did not point to the statistical association between alcohol and SF. Malacco et al demonstrated, in a murine model of aspergillosis, that chronic alcohol consumption reduces neutrophils' recruitment to the lungs, favouring fungal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 On the other hand, Fichman et al found that 78.6% of patients using alcohol in a cohort of 12 patients with pulmonary sporotrichosis. 7 Besides reporting the alcohol consumption by the patients, those studies did not point to the statistical association between alcohol and SF. Malacco et al demonstrated, in a murine model of aspergillosis, that chronic alcohol consumption reduces neutrophils' recruitment to the lungs, favouring fungal growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, atypical and more severe manifestations of sporotrichosis have been associated with S . brasiliensis 7,16–18 …”
Section: Introductionmentioning
confidence: 99%
“…Systemic infections, such as pulmonary sporotrichosis, are rare and usually are established in immunosuppressed patients [ 1 ]. Fichman et al reported here a 22-year, retrospective cohort study on pulmonary sporotrichosis carried out in the Instituto Nacional de Infectologia Evandro Chagas (Rio de Janeiro, Brazil), and found that during the analyzed period, only 14 patients fulfilled all the inclusion criteria (all of which were diagnosed with an S. brasiliensis -caused infection) [ 16 ]. This is a surprising figure considering that the clinical center is placed in the heart of a sporotrichosis hyperepidemic area.…”
mentioning
confidence: 99%
“…This is a surprising figure considering that the clinical center is placed in the heart of a sporotrichosis hyperepidemic area. Primary pulmonary sporotrichosis was observed only in 7.1% of patients, whilst the rest were associated with disseminated infection [ 16 ]. Human immunodeficiency virus infection, alcoholism, and chronic obstructive pulmonary disease were the main comorbidities in these patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation